Cell Population–resolved Multiomics Atlas of the Developing Lung - Ushakumary, Mereena G.; Feng, Song; Bandyopadhyay, Gautam; Olson, Heather; Weitz, Karl K.; Huyck, Heidi L.; Poole, Cory; Purkerson, Jeffrey M.; Bhattacharya, Soumyaroop; Ljungberg, M. Cecilia; Mariani, Thomas J.; Deutsch, Gail H.; et al. (American journal of respiratory cell and molecular biology, 2025)
The lung is a vital organ that undergoes extensive morphological and functional changes during postnatal development. To disambiguate how different cell populations contribute to organ development, we performed proteomic and transcriptomic analyses of four sorted cell populations from the lung of human subjects 0-8 years of age with a focus on early life. The cell populations analyzed included epithelial, endothelial, mesenchymal, and immune cells. Our results revealed distinct molecular signatures for each of the sorted cell populations that enable the description of molecular shifts occurring in these populations during postnatal development. We confirmed that the proteome of the different cell populations was distinct regardless of age and identified functions specific to each population. We identified a series of cell population protein markers, including those located at the cell surface, that show differential expression and distribution on RNA hybridization and immunofluorescence imaging. We validated the spatial distribution of alveolar type 1 and endothelial cell surface markers. Temporal analyses of the proteomes of the four populations revealed processes modulated during postnatal development and clarified the findings obtained from whole-tissue proteome studies. Finally, the proteome was compared with a transcriptomics survey performed on the same lung samples to evaluate processes under post-transcriptional control.